Patterns of change in permanganate oxidizable soil organic matter from semiarid drylands reflected by absorbance spectroscopy and Fourier transform ion cyclotron resonance mass spectrometry. (June 2018) - Romero, Carlos M.; Engel, Richard E.; D'Andrilli, Juliana; Chen, Chengci; Zabinski, Catherine; Miller, Perry R.; Wallander, Roseann
Highlights: The permanganate-oxidizable carbon (POXC) fraction was analyzed. Heteroatom compounds in aqueous extracts were identified by FT-ICR MS. POXC may not provide a clear advantage over organic carbon as a quality indicator. POXC is best described as a complex mixture of KMnO4 -reactive organic matter. Abstract: Organic matter (OM) oxidized by slightly alkaline KMnO4, termed permanganate-oxidizable carbon (POXC), has recently emerged as a standardized indicator of active, labile carbon within soil quality frameworks. Yet, qualitative information on POXC, particularly in semiarid drylands, is very scarce. The aim of this study was to characterize POXC within three long-term field experiments in Montana, USA: (i) across a wide range of edaphic (e.g., % clay) and management conditions (e.g., cropping intensity) ( n = 148); and (ii) to identify the molecular composition of soil OM before and after KMnO4 treatment using electrospray ionization Fourier transform ion cyclotron resonance mass spectrometry (ESI FT-ICR MS). The content of POXC was significantly greater under perennial (382–685 mg/kg) or annual cropping (404–607 mg/kg) than fallow-wheat (359–543 mg/kg) systems. Soil OM changes, however, were equally or better expressed when considering soil organic carbon (SOC) concentration. The occurrence of POXC paralleled SOC ( R = 0.87; P < 0.001) and total nitrogen (TN) ( R = 0.82; P < 0.001) concentrations, regardless of soil textural differences. The ESI FT-ICR MS analyses of aqueous soil extracts indicated that the KMnO4 reaction oxidized dissolved OM of diverse molecular character. OM molecular composition after KMnO4 treatment was enriched by strongly reduced chemical constituents (O/C < 0.4) at greater condensed aromaticity (AI > 0.67) and hydrogen saturation (aliphatic composition; H/C > 1.5) across all heterogeneous groups (Cc Hh Nn Oo Ss ). Although POXC is a rapid assay widely used for characterizing soil OM dynamics, it may not provide a clear advantage over SOC concentration in semiarid drylands. The view of POXC as a merely labile, simple biodegradable OM fraction needs to be reconsidered.